PCR Detection for Epstein-Bar Virus Associated with Leukemia Patients in Babylon Province of Iraq - Mohammed T. Al-Tameemi (Journal of Global Pharma Technology, 2019)
The first virus to be implicated in the causation of a human cancer was the Epstein–Barr virus (EBV), discovered in 1964 by Epstein, and Barr in a lymphoid cell line established from a biopsy of an African Burkitt lymphoma. The present study establish  for detection Epstein-Bar virus  in thirty serum samples  collected from Marjan hospital in Babylon Province of Iraq. Detection of this virus conducted by polymerase chain reaction for blood diagnosed firstly as having Epstein-Bar virus with leukemia by ELISA technique. Twenty three from thirty samples are positive for EBV association with leukemia patients according to PCR produced 161 bp band referred to EBV gene noticed at gel electrophoresis technique. Keywords: Epstein–Barr virus, Leukemia, PCR.